Pelatihan Ramah Lingkungan dan Kinerja Berkelanjutan: Peran Mediasi Keterlibatan Karyawan di Kalangan Karyawan PT. XYZ - Purwatiningsih Purwatiningsih; Bahtiar Efendi Efendi (Jurnal Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the effect of green training on sustainable performance, with employee engagement as a mediating variable, among employees of PT. Holcim Indonesia. The research approach employed a quantitative method with an explanatory design, and data collection was conducted through a questionnaire survey of permanent employees who had participated in the company's training program. The sample size was 150 respondents, selected using a probability sampling technique. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results showed that green training had a positive and significant effect on employee engagement and sustainable performance. Employee engagement was also shown to have a positive effect on sustainable performance. Furthermore, employee engagement acted as a partial mediator in the relationship between green training and sustainable performance. These findings indicate that implementing green training not only improves employees' environmental competence and awareness but also strengthens their engagement, which impacts the company's economic, social, and environmental performance. This research provides theoretical contributions to the development of Green Human Resource Management literature and practical contributions to company management in designing training strategies that support organizational sustainability.